Peningkatan Kesejahteraan Petani Kopi Desa Ketindan Melalui Pertanian Regeneratif Pupuk Organik Plus - Sari, Dina Kartika; Rianti, Titis Surya Maha (Universitas Dinamika, 2025)
Ketindan Village is one of the producers of robusta coffee in Malang Regency, the problem faced by coffee farmers in Ketindan Village is the low quality of the coffee produced. Community service activities for the Sumber Rejeki Farmers Group located in Lawang District, Malang Regency, precisely in Ketindan Village, aim to provide education to coffee farmers, especially about the use of goat manure and coffee skin waste by processing it into organic fertilizer plus. The service method used in this service activity is a workshop with the delivery of materials and direct practice of making organic fertilizer plus and applying compost fertilizer plus to plants. Based on the results of the training activities on making organic fertilizer plus, it can be said that everything went according to plan. The knowledge of farmers, especially coffee farmers, about organic fertilizer is increasing. The results showed an average increase in knowledge and understanding of 66%. With the implementation of the provision of organic fertilizer, the harvest produced will be of much better quality. This is in line with improving the welfare of coffee farmers' standard of living. In the future, education can be carried out in the post-harvest processing process of coffee in increasing the price of coffee at the consumer level.